Giovani Jeunes Jovenes - Gianfranco, Bettin Lattes (Studi e saggi, 2001)
The book illustrates the results of research that emerged within the context of a specific European Union programme. The analysis was carried out by Italian, French and Spanish academics co-ordinated by the Inter-University Centre of Political Sociology of the University of Florence. It aims to reconstruct the educational careers of the new generations within the social and economic context of Southern Europe, paying particular attention to the conditions of university students and to youth unemployment. The issue is examined and discussed also in relation to a broader sociological meditation on the values shaping the future of the political culture in contemporary Europe.